2019
DOI: 10.1038/s41587-019-0324-7
|View full text |Cite
|
Sign up to set email alerts
|

Access and openness in biotechnology research collaborations between universities and industry

Abstract: Uploaded to CBS Research Portal in accordance with the self-archiving policy of Nature Research * This version of the article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the publisher's final version AKA Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Further collaborations between scientists from academia and industry (in addition to researchers from government agencies) [18] would help to facilitate the development of novel methods, and aid in promoting their implementation around the world. For many countries, the main barrier to the broad use of molecular methods is the high cost of equipment and reagents [19].…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Further collaborations between scientists from academia and industry (in addition to researchers from government agencies) [18] would help to facilitate the development of novel methods, and aid in promoting their implementation around the world. For many countries, the main barrier to the broad use of molecular methods is the high cost of equipment and reagents [19].…”
Section: Additional Considerationsmentioning
confidence: 99%
“…It is thus unsurprising that the literature suggests that the move to university-owned and controlled patents, accelerated, in part, through the 1980 Bayh-Dole Act ( Mowery et al., 2001 ), did not demonstrably achieve either of the two overarching goals of the practice: to increase the level of innovation in the economy and to increase revenue gains for universities ( Eisenberg and Cook-Deegan, 2018 ; Ouellette and Tutt, 2020 ; Corredoira et al., 2019 ). There are several reasons put forward to explain why a university patenting strategy has not had the desired results, including decreased downstream development and upstream duplication ( Egelie et al., 2019 ), increased difficulty and delays in establishing contractual relationships with university technology transfer offices ( Dahlborg et al., 2017 ; Hertzfeld et al., 2006 ; Kira R. Fabrizio, 2006 ), lack of university expertise and market knowledge ( Swamidass and Vulasa, 2009 ), delayed dissemination and uptake of results ( Williams, 2013 ; Fabrizio, 2009 ; Kira, 2006 ; West, 2006 ), perverse university incentive structures ( Ouellette and Tutt, 2020 ; Eisenberg and Cook-Deegan, 2018 ) and the use of university patents to sue firms that have developed products without the aid of university patents ( Eisenberg and Cook-Deegan, 2018 , 82; Rooksby, 2011 ).…”
Section: Explanations For the Declinementioning
confidence: 99%
“…Universities, colleges and research institutes have demonstrated no particular skill at managing intellectual property ( Egelie et al., 2019 ). Thus, the lack of patents within OSPs – in which universities and research institutes are important players – comes at little cost.…”
Section: Innovating the Innovation System Through Open Science Partnershipsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a complement to the focus on later stages of the scientific research process in OS, OI emphasises processes and logics of exchange in the early and intermediary steps of knowledge production. Of late, OI-influenced researchers have specifically explored these dynamics in the context of science (Beck et al 2020;Franzoni and Sauermann 2014;Guinan, Boudreau, and Lakhani 2013;Lifshitz-Assaf 2018), extending the linkages between OI and the science context beyond different forms of technology transfer (Chesbrough 2020;Egelie et al 2019;Perkmann et al 2013). However, despite potential synergies between the OS and OI approaches, our understanding of open and collaborative practices in the science context and their related antecedents, consequences, and contingencies remains limited and fragmented.…”
Section: Introductionmentioning
confidence: 99%